Preparation method and application of macroporous silica-alumina gel

Large pores are produced by adding aluminum salts and additives to sodium metasilicate solution and adding an acid solution of the template agent under stirring to form a silica gel, which is then aged, filtered, dried and calcined in a microwave reactor. Silicon-aluminum glue solves the problems of limited increase in aluminum content, high cost or small pore size in the existing silicon-aluminum glue preparation methods, and realizes high specific surface area, high pore capacity and uniform particle size silicon-aluminum glue, suitable for catalytic ethylene polymerization reaction.

CN119409201APending Publication Date: 2025-02-11QINZHOU DONGCHEN MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411534633.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing preparation methods for silicon-aluminum adhesives have problems such as limited increase in aluminum content, high cost or small pore size, which limits its widespread use in high-temperature environments and industrial applications.

Method used

Large pores are produced by adding aluminum salts and additives to sodium metasilicate solution and adding an acid solution of the template agent under stirring to form a silica gel, which is then aged, filtered, dried and calcined in a microwave reactor. Silicon-aluminum glue.

Benefits of technology

The high specific surface area, high pore volume and uniform particle size of macroporous silicon-aluminum glue are achieved, which is suitable for catalyzing ethylene polymerization, and improves the activity of the catalyst and the quality of the polymer.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of macroporous silica-alumina gel. The preparation method comprises the following steps: (1) adding a template agent into an acid solution, and stirring to prepare an acid solution containing the template agent; (2) adding an aluminum salt and an auxiliary agent into the sodium metasilicate solution, then adding an acid solution containing a template agent, and then dropwise adding the acid solution to prepare silica-alumina gel; (3) putting the silica-alumina gel into a microwave reactor for aging; (4) drying the aged silica-alumina gel to prepare powder, and removing the template agent to prepare silica-alumina gel; (5) soaking silica-alumina gel in a salt solution to obtain silica-alumina gel subjected to double salt treatment; and (6) dipping the silica-alumina gel subjected to double salt treatment in aqua regia to obtain a solid, washing, drying and roasting. The preparation method of the macroporous silica-alumina gel provided by the invention has the advantages of simple operation, cheap and easily available raw materials and the like, and the prepared macroporous silica-alumina gel particles also have high specific surface area and high pore volume. The silica-alumina gel prepared by the invention can be successfully applied to catalytic ethylene polymerization reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silica-alumina gel, and in particular relates to a preparation method of macroporous silica-alumina gel and application thereof. Background Art

[0002] In the field of materials science and chemical engineering, porous materials have attracted extensive attention due to their unique pore structure and adjustable chemical properties. Among them, silica-based porous materials have shown great application potential in catalysis, adsorption, separation and thermal insulation. Ordinary silica gel is a porous material composed of silicon radicals. It is considered to be an excellent catalyst carrier and adsorbent due to its high specific surface area and good thermal stability. However, the mechanical strength and stability of ordinary silica gel in high temperature environments limit its use in a wider range of applications. For example, the mechanical strength and stability of ordinary silica gel will be significantly reduced when the temperature is higher than 600°C. In order to overcome these limitations, one of the feasible methods is to introduce alumina (Al2O3) into the silica gel matrix. 2 O 3 ) to prepare silica-alumina gel materials. Silica-alumina gel composite materials not only have the high porosity of silica gel, but also have the high temperature stability of alumina (the introduction of alumina phase can increase the thermal stability of the obtained silica-alumina gel material to between 1200-1400℃), thus showing advantages in a wider range of industrial applications. (Cláudio MRAlmeida, Mariana E.Ghica, Luísa An overview on alumina-silica-based aerogels[J]. Advances in Colloid and Interface Science. 2020, 282.).

[0003] At present, the following three methods are mainly used to prepare silica-alumina gel in industrial production: The first method is to add a small amount of aluminum salt during the production of silica gel, and then generate silica-alumina gel through hydrolysis reaction: However, this method has limitations on the increase of aluminum content, because too high aluminum content may have an adverse effect on the pore structure of silica-alumina gel, and the amount of aluminum added is usually controlled below 20%. The second method is to use a template method to prepare silica-alumina gel with a larger pore size, such as the SIRAL series produced by Sasol in Germany, but the cost of this method is relatively high. The third method is to use a carbonization method to mix aluminum salts and silicon-containing compounds with carbon dioxide gas to form a gel. In this process, a pH swing method is used to introduce a silicon source, but the silica-alumina gel prepared by this method has a smaller pore size. In view of this, this patent application is specially proposed. Summary of the invention

[0004] The purpose of the present invention is to provide a macroporous silica-alumina gel and a preparation method and application thereof.

[0005] In order to achieve the above object, the solution of the present invention is:

[0006] A method for preparing macroporous silica-alumina gel specifically comprises the following steps:

[0007] (1) adding the template agent into the acid solution and stirring evenly to prepare an acid solution containing the template agent;

[0008] (2) adding aluminum salt and an auxiliary agent to the sodium metasilicate solution, and then adding the acid solution containing the template agent prepared in step (1) under stirring, stirring the mixture sufficiently to react, and then continuously adding the acid solution dropwise to the obtained mixture to prepare a silica-alumina gel;

[0009] (3) placing the silica-alumina gel obtained in step (2) into a microwave reactor for aging, and filtering to obtain an aged silica-alumina gel;

[0010] (4) drying the aged alumina-silica gel obtained in step (3) to obtain a powder, and removing the template agent from the obtained powder to obtain alumina-silica gel;

[0011] (5) soaking the silica-alumina gel prepared in step (4) in a salt solution to obtain a silica-alumina gel treated with double salt;

[0012] (6) The silica-alumina colloid treated with double salt obtained in step (5) is added to aqua regia for immersion, and the obtained solid is washed, dried and then calcined to obtain the macroporous silica-alumina colloid.

[0013] Preferably, the template agent in step (1) is one of carbon microspheres or polystyrene microspheres.

[0014] Preferably, the aluminum salt described in step (2) is one of aluminum trichloride, aluminum sulfate or aluminum nitrate.

[0015] Preferably, the auxiliary agent in step (2) is one of citric acid, oxalic acid, tartaric acid or acetic acid.

[0016] Preferably, the acidic solution in step (2) is one of ammonium chloride solution, sulfuric acid solution or hydrochloric acid solution.

[0017] Preferably, the microwave reaction conditions described in step (3) are as follows: microwave power is 250-300W, reaction temperature is 60-80°C, and reaction time is 1-3h.

[0018] Preferably, the salt solution described in step (5) is a complex salt solution composed of sodium chloride, lithium chloride and potassium chloride.

[0019] Preferably, the calcination conditions in step (6) are: calcination temperature is 600-1000° C.; calcination time is 4-8 h.

[0020] The macroporous silica-alumina gel prepared by the above-mentioned preparation method has a specific surface area of ​​350-550m 2 / g, the pore volume is 2.3~3.5mL / g, and the average particle size is 80~130μm.

[0021] The macroporous silica-alumina gel prepared by the above preparation method is used in catalyzing ethylene polymerization reaction.

[0022] The principle of the present invention is as follows:

[0023] The preparation method of the macroporous silica-alumina gel provided by the present invention is completely different from the traditional impregnation method; specifically, the traditional impregnation method is to first synthesize silica gel and then load the aluminum source onto the silica gel in a certain proportion. The amount of aluminum loaded by this method is limited and the distribution of metal aluminum in the silica gel is not uniform enough, because too much aluminum will cause the silica gel gap to be blocked and the pore volume to be reduced. The method provided by the present invention is to add a water-soluble aluminum salt to a silicon source (sodium metasilicate) to prepare silica-alumina gel by a sol-gel method; during the reaction process, the size of the prepared silica-alumina gel and the size of the pores can be adjusted by adjusting the size of the template agent, and adding an organic acid as an auxiliary agent to the sol-gel reaction can effectively adjust the hydrolysis rate of the silicon source, thereby reducing the agglomeration of aluminum oxide during the hydrolysis process, and allowing the metal aluminum to be more evenly dispersed in the skeleton network of silicon in the silica-alumina gel.

[0024] Compared with the existing method for preparing silica-alumina gel, the gain effect of the present invention is as follows:

[0025] 1. The preparation method of the macroporous silica-alumina gel provided by the present invention not only has the advantages of simple operation and cheap and readily available raw materials, but the prepared macroporous silica-alumina gel particles also have the advantages of high specific surface area and high pore volume.

[0026] 2. The macroporous silica-alumina gel prepared by the preparation method of the present invention can be used to prepare a carrier of a chromium-based catalyst. The prepared catalyst not only has a high MI potential, but can also produce more high molecular weight polymers.

[0027] 3. The catalyst prepared using the macroporous silica-alumina gel provided by the present invention as a carrier can be successfully used to catalyze ethylene polymerization reactions; the results show that the activity of the catalyst is 4206 gPE / gcat / h; the MI of the obtained polyethylene product is 0.08 dg / min; the HLMI of the obtained polyethylene product is 13.1 dg / min; and the density of the obtained polyethylene product is 0.9548 g / ml. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. The specific quality, reaction time and temperature, process parameters, etc. in the examples are only examples within the appropriate ranges, and some non-essential improvements and adjustments made by those skilled in the art according to the above content of the present invention all belong to the scope of protection of the present invention.

[0029] All reagents used were commercial reagents unless otherwise specified and were not further purified before use.

[0030] The partial melt index (MI) of the embodiment of the present invention is measured according to the standard ASTM D1238-E, and the specific conditions are: 190 / 2, at 190° C., with a weight of 2160 g, and the unit is g / 10 min.

[0031] The high load melt index (HLMI) of the embodiments of the present invention is measured according to the standard ASTM D1238-F, and the specific conditions are: 190 / 21.6, at 190° C., with a weight of 21600 g, and the unit is g / 10min.

[0032] The density of some polymers in the examples of the present invention is measured according to procedure C in standard ASTM D1505-68 and ASTM D1928. The specific operation is: the polymer is melt-molded and sampled, the sample is cooled at a rate of 15°C / hr, and the sample is stored at room temperature for about 40 hours before being measured, and the density is expressed as the weight of the polymer per cubic centimeter (g / cc).

[0033] Embodiment 1:

[0034] The preparation steps of macroporous silica-alumina gel are as follows:

[0035] (1) adding 2.5 g of carbon microspheres (particle size range 10-40 μm) into 90 ml of 1 mol / L hydrochloric acid solution and stirring the mixture to obtain a hydrochloric acid solution containing carbon microspheres;

[0036] (2) 8 g of sodium metasilicate was dissolved in 30 ml of deionized water, 2 g of aluminum chloride and 0.6 g of citric acid were added to the obtained sodium metasilicate solution in sequence, and then the hydrochloric acid solution containing carbon microspheres prepared in step (1) was added under stirring. After sufficient stirring, a white colloid was produced in the solution. Under continued stirring, 0.1 mol / L of ammonium chloride solution was added dropwise to the obtained mixture until the white colloid disappeared to obtain a silica-alumina gel;

[0037] (3) placing the silica-alumina gel obtained in step (2) into a microwave reactor for aging reaction, setting the microwave power to 450 W, and aging the reaction at a reaction temperature of 70° C. for 1 h, and filtering to obtain the aged silica-alumina gel;

[0038] (4) placing the aged alumina-silica gel obtained in step (3) in a vacuum drying oven and drying at 110° C. for 6 h, then grinding the aged alumina-silica gel into powder, transferring the obtained powder into a dielectric barrier discharge device for low-temperature plasma treatment to remove carbon microspheres, wherein the plasma treatment is carried out in an oxygen atmosphere at a temperature of 220° C., and the alumina-silica gel from which carbon microspheres are removed is obtained after treatment at a voltage of 220 V and a current of 3.5 A for 3 h;

[0039] (5) The silica-alumina gel from which the carbon microspheres were removed was placed in 300 ml of a double salt solution consisting of NaCl, LiCl and KCl (the mass ratio of NaCl, LiCl, KCl and water was H 2 O:NaCl:LiCl:KCl=70:15:5:10) and stirred evenly; then put it into an ultrasonic oscillator, set the ultrasonic frequency to 80kHz, the power to 50w, and perform ultrasonic immersion at 45°C for 1h to obtain silica-alumina gel after double salt treatment;

[0040] (6) Immerse the silica-alumina gel after the double salt treatment obtained in step (5) into 100 ml of aqua regia for de-sodium treatment, and immerse for about 6 hours. It should be noted that this step cannot use a glass container, and a polytetrafluoroethylene container must be used for immersion; after immersion, filter and collect the obtained solid; wash the obtained solid with deionized water until it is neutral (check with silver nitrate solution to see that there is no chloride ion), then place it in a vacuum drying oven and dry it at 110°C for 10 hours, place the dried solid in a muffle furnace, roast it at 950°C for 6 hours, and then cool it to room temperature to obtain the macroporous silica-alumina gel; the obtained macroporous silica-alumina gel is recorded as Al-SG-1. The prepared silica-alumina gel was characterized, and the results are as follows: the specific surface area of ​​the silica-alumina gel is 491m2 / g, the pore volume is 2.54ml / g, and the average particle size is 125.7μm.

[0041] Example 2

[0042] The preparation steps of macroporous silica-alumina colloid supported chromium catalyst are as follows:

[0043] 2.75g of the macroporous silica-alumina gel Al-SG-1 prepared in Example 1 was weighed and placed in an oven at 110°C for 4 hours for drying, and then added to a dry flask. A mixed solution consisting of 0.179g of acetylacetonato chromium, 0.213g of basic aluminum acetate (stabilized by 1% boric acid) and 7.5ml of methanol was added to the flask under nitrogen protection; the obtained mixture was subjected to ultrasonic oscillation at room temperature, wherein the ultrasonic oscillation power was 250w, the ultrasonic oscillation frequency was 80kHz, and the reaction time was 30min. After filtering, the obtained solid was placed in a vacuum drying oven and dried at 110°C for 12h to obtain a macroporous silica-alumina gel-supported chromium catalyst, totaling 2.62g, and the obtained catalyst was recorded as Cr / Al-SG-1. The detection results of the metal components in the prepared catalyst are as follows: the content of Cr is 1.08%, and the content of metal Al is 9.45%.

[0044] Example 3

[0045] The specific steps of ethylene polymerization are as follows:

[0046] Under nitrogen protection, 0.04g of catalyst Cr / Al-SG-1 was added to a dry polymerization reaction bottle, followed by 2400g of isobutane liquid, and the reaction bottle was heated to about 105°C; then ethylene gas was introduced into the reaction bottle, and the reaction pressure was maintained at 3.65MPa, and the pressure was maintained constant during the reaction; the reaction was stopped after continuous stirring for 1h, and the reaction polymer powder was recovered; then, the obtained polymer powder was fully dried and weighed for characterization, and the activity of the Cr / Al-SG-1 catalyst was expressed by the weight of the polymer produced per gram of catalyst per hour (gram polyethylene / gram catalyst / hour). The specific characterization results are as follows: the activity of the catalyst Cr / Al-SG-1 is 4070gPE / gcat / h; the melt index MI of the obtained polyethylene product is 0.08dg / min; the high load melt index HLMI of the obtained polyethylene product is 12.4dg / min; the density of the obtained polyethylene product is 0.9546g / ml.

[0047] Embodiment 4:

[0048] The preparation steps of macroporous silica-alumina gel refer to Example 1, except that the carbon microspheres in step (1) are replaced with polystyrene microspheres (particle size 30 μm), and the remaining steps are the same as Example 1. The obtained macroporous silica-alumina gel is recorded as Al-SG-2. The prepared silica-alumina gel is characterized, and the results are as follows: the specific surface area of ​​the silica-alumina gel is 507 m2 / g, the pore volume is 2.63 ml / g, and the average particle size is 109.7 μm.

[0049] The preparation steps of the macroporous silica-alumina gel supported chromium catalyst refer to Example 2, except that the silica-alumina gel Al-SG-1 is replaced by Al-SG-2, and the remaining steps are the same as Example 2, and the obtained catalyst is recorded as Cr / Al-SG-2. The detection results of the metal components in the prepared catalyst are as follows: the content of Cr is 1.10%, and the content of metal Al is 9.86%.

[0050] The steps of catalyzing ethylene polymerization reaction refer to Example 3, except that the catalyst Cr / Al-SG-1 is replaced by Cr / Al-SG-2; the catalytic results are: the activity of catalyst Cr / Al-SG-2 is 4128gPE / gcat / h; the MI of the obtained polyethylene product is 0.08dg / min; the HLMI of the obtained polyethylene product is 12.7dg / min; the density of the obtained polyethylene product is 0.9545g / ml.

[0051] Embodiment 5:

[0052] The preparation steps of macroporous silica-alumina gel refer to Example 1, except that the citric acid in step (2) is replaced by oxalic acid, and the remaining steps are the same as Example 1, and the obtained macroporous silica-alumina gel is recorded as Al-SG-3. The prepared silica-alumina gel is characterized, and the results are as follows: the specific surface area of ​​the silica-alumina gel is 477m2 / g, the pore volume is 2.43ml / g, and the average particle size is 120.2μm.

[0053] The preparation steps of the macroporous silica-alumina gel supported chromium catalyst refer to Example 2, except that the silica-alumina gel Al-SG-1 is replaced by Al-SG-3, and the remaining steps are the same as Example 2, and the obtained catalyst is recorded as Cr / Al-SG-3. The detection results of the metal components in the prepared catalyst are as follows: the content of Cr is 1.05%, and the content of metal Al is 9.22%.

[0054] The steps of catalyzing ethylene polymerization reaction refer to Example 3, except that the catalyst Cr / Al-SG-1 is replaced by Cr / Al-SG-3; the catalytic results are: the activity of catalyst Cr / Al-SG-3 is 3851gPE / gcat / h; the MI of the obtained polyethylene product is 0.07dg / min; the HLMI of the obtained polyethylene product is 10.6dg / min; the density of the obtained polyethylene product is 0.9543g / ml.

[0055] Embodiment 6:

[0056] The preparation steps of macroporous silica-alumina gel refer to Example 1, except that the citric acid in step (2) is replaced by tartaric acid, and the remaining steps are the same as Example 1, and the obtained macroporous silica-alumina gel is recorded as Al-SG-4. The prepared silica-alumina gel is characterized, and the results are as follows: the specific surface area of ​​the silica-alumina gel is 502m2 / g, the pore volume is 2.71ml / g, and the average particle size is 117.8μm.

[0057] The preparation steps of the macroporous silica-alumina gel supported chromium catalyst refer to Example 2, except that the silica-alumina gel Al-SG-1 is replaced by Al-SG-4, and the remaining steps are the same as Example 2, and the obtained catalyst is recorded as Cr / Al-SG-4. The detection results of the metal components in the prepared catalyst are as follows: the content of Cr is 1.12%, and the content of metal Al is 9.92%.

[0058] The steps of catalyzing ethylene polymerization reaction refer to Example 3, except that the catalyst Cr / Al-SG-1 is replaced by Cr / Al-SG-4; the catalytic results are: the activity of catalyst Cr / Al-SG-4 is 4206gPE / gcat / h; the MI of the obtained polyethylene product is 0.08dg / min; the HLMI of the obtained polyethylene product is 13.1dg / min; the density of the obtained polyethylene product is 0.9546g / ml.

[0059] Embodiment 7:

[0060] The preparation steps of macroporous silica-alumina gel refer to Example 1, except that the citric acid in step (2) is replaced by acetic acid, and the remaining steps are the same as Example 1, and the obtained macroporous silica-alumina gel is recorded as Al-SG-5. The prepared silica-alumina gel is characterized, and the results are as follows: the specific surface area of ​​the silica-alumina gel is 468m2 / g, the pore volume is 2.38ml / g, and the average particle size is 123.0μm.

[0061] The preparation steps of the macroporous silica-alumina gel supported chromium catalyst refer to Example 2, except that the silica-alumina gel Al-SG-1 is replaced by Al-SG-5, and the remaining steps are the same as Example 2, and the obtained catalyst is recorded as Cr / Al-SG-5. The detection results of the metal components in the prepared catalyst are as follows: the content of Cr is 1.04%, and the content of metal Al is 9.18%.

[0062] The steps of catalyzing ethylene polymerization reaction refer to Example 3, except that the catalyst Cr / Al-SG-1 is replaced by Cr / Al-SG-5; the catalytic results are: the activity of catalyst Cr / Al-SG-5 is 3770gPE / gcat / h; the MI of the obtained polyethylene product is 0.07dg / min; the HLMI of the obtained polyethylene product is 9.9dg / min; the density of the obtained polyethylene product is 0.9544g / ml.

[0063] Embodiment 8:

[0064] The preparation steps of macroporous silica-alumina gel refer to Example 1, except that the operation of step (3) is changed to: the silica-alumina gel prepared in step (1) is placed in a stainless steel reactor and sealed for aging reaction at 100°C for 24 hours, after the reaction is completed, the reaction is cooled to room temperature and filtered to obtain the aged silica-alumina gel; the remaining steps are the same as Example 1, and the obtained macroporous silica-alumina gel is recorded as Al-SG-6. The prepared silica-alumina gel is characterized, and the results are as follows: the specific surface area of ​​the silica-alumina gel is 466m2 / g, the pore volume is 2.39ml / g, and the average particle size is 124.5μm.

[0065] The preparation steps of the macroporous silica-alumina gel supported chromium catalyst refer to Example 2, except that the silica-alumina gel Al-SG-1 is replaced by Al-SG-6, and the remaining steps are the same as Example 2, and the obtained catalyst is recorded as Cr / Al-SG-6. The detection results of the metal components in the prepared catalyst are as follows: the content of Cr is 1.07%, and the content of metal Al is 9.41%.

[0066] The steps of catalyzing ethylene polymerization reaction refer to Example 3, except that the catalyst Cr / Al-SG-1 is replaced by Cr / Al-SG-6; the catalytic results are: the activity of catalyst Cr / Al-SG-6 is 3991gPE / gcat / h; the MI of the obtained polyethylene product is 0.08dg / min; the HLMI of the obtained polyethylene product is 12.5dg / min; the density of the obtained polyethylene product is 0.9545g / ml.

[0067] Embodiment 9:

[0068] The preparation steps of macroporous silica-alumina gel refer to Example 1, except that the operation of step (4) is changed to: the aged silica-alumina gel prepared in step (3) is placed in a vacuum drying oven and dried at 110°C for 6 hours and then ground into powder, and the obtained powder is placed in a muffle furnace and calcined at 900°C for 12 hours to obtain silica-alumina gel with carbon microspheres removed; the remaining steps are the same as Example 1, and the obtained macroporous silica-alumina gel is recorded as Al-SG-7. The prepared silica-alumina gel is characterized, and the results are as follows: the specific surface area of ​​the silica-alumina gel is 452m2 / g, the pore volume is 2.31ml / g, and the average particle size is 110.4μm.

[0069] The preparation steps of the macroporous silica-alumina gel supported chromium catalyst refer to Example 2, except that the silica-alumina gel Al-SG-1 is replaced by Al-SG-7, and the remaining steps are the same as Example 2, and the obtained catalyst is recorded as Cr / Al-SG-7. The detection results of the metal components in the prepared catalyst are as follows: the content of Cr is 1.01%, and the content of metal Al is 9.13%.

[0070] The steps of catalyzing ethylene polymerization reaction refer to Example 3, except that the catalyst Cr / Al-SG-1 is replaced by Cr / Al-SG-7; the catalytic results are: the activity of catalyst Cr / Al-SG-7 is 3630gPE / gcat / h; the MI of the obtained polyethylene product is 0.07dg / min; the HLMI of the obtained polyethylene product is 9.4dg / min; the density of the obtained polyethylene product is 0.9540g / ml.

[0071] Embodiment 10:

[0072] The preparation steps of macroporous silica-alumina gel refer to Example 1, except that step (5) is omitted and the silica-alumina gel obtained in step (4) without carbon microspheres is directly subjected to step (6); the remaining steps are the same as in Example 1, and the obtained macroporous silica-alumina gel is recorded as Al-SG-8. The prepared silica-alumina gel is characterized, and the results are as follows: the specific surface area of ​​the silica-alumina gel is 393m2 / g, the pore volume is 2.02ml / g, and the average particle size is 108.7μm.

[0073] The preparation steps of the macroporous silica-alumina gel supported chromium catalyst refer to Example 2, except that the silica-alumina gel Al-SG-1 is replaced by Al-SG-8, and the remaining steps are the same as Example 2, and the obtained catalyst is recorded as Cr / Al-SG-8. The detection results of the metal components in the prepared catalyst are as follows: the content of Cr is 0.96%, and the content of metal Al is 9.05%.

[0074] The steps of catalyzing ethylene polymerization reaction refer to Example 3, except that the catalyst Cr / Al-SG-1 is replaced by Cr / Al-SG-8; the catalytic results are: the activity of catalyst Cr / Al-SG-8 is 3025gPE / gcat / h; the MI of the obtained polyethylene product is 0.07dg / min; the HLMI of the obtained polyethylene product is 8.7dg / min; the density of the obtained polyethylene product is 0.9541g / ml.

[0075] Comparative Example 1

[0076] The preparation steps of the chromium catalyst refer to Example 2, except that the silica gel Al-SG-1 is replaced with ordinary commercially available 955 silica gel powder, and the remaining steps are the same as Example 2, and the obtained catalyst is recorded as Cr / Al-SG-9. The detection results of the metal components in the prepared catalyst are as follows: the loading amount of Cr is 0.84%, and the loading amount of metal Al is 1.36%.

[0077] The steps of catalyzing the ethylene polymerization reaction refer to Example 3, except that the catalyst Cr / Al-SG-1 is replaced by Cr / Al-SG-9; the catalytic results are: the activity of the catalyst Cr / Al-SG-9 is 1910 gPE / gcat / h; the MI of the obtained polyethylene product is 0.07 dg / min; the HLMI of the obtained polyethylene product is 7.3 dg / min; the density of the obtained polyethylene product is 0.9540 g / ml.

Claims

1. A method for preparing macroporous silica-alumina gel, characterized in that: The specific steps include: (1) adding the template agent into the acid solution and stirring evenly to prepare an acid solution containing the template agent; (2) adding aluminum salt and an auxiliary agent to the sodium metasilicate solution, and then adding the acid solution containing the template agent prepared in step (1) under stirring, stirring the mixture sufficiently to react, and then continuously adding the acid solution dropwise to the obtained mixture to prepare a silica-alumina gel; (3) placing the silica-alumina gel obtained in step (2) into a microwave reactor for aging, and filtering to obtain an aged silica-alumina gel; (4) drying the aged alumina-silica gel obtained in step (3) to obtain a powder, and removing the template agent from the obtained powder to obtain alumina-silica gel; (5) soaking the silica-alumina gel prepared in step (4) in a salt solution to obtain a silica-alumina gel treated with double salt; (6) The silica-alumina colloid treated with double salt obtained in step (5) is added to aqua regia for immersion, and the obtained solid is washed, dried and then calcined to obtain the macroporous silica-alumina colloid.

2. The method for preparing macroporous silica-alumina gel according to claim 1, characterized in that: The template agent described in step (1) is one of carbon microspheres or polystyrene microspheres.

3. The method for preparing macroporous silica-alumina gel according to claim 1, characterized in that: The aluminum salt described in step (2) is one of aluminum trichloride, aluminum sulfate or aluminum nitrate.

4. The method for preparing macroporous silica-alumina gel according to claim 1, characterized in that: The auxiliary agent in step (2) is one of citric acid, oxalic acid, tartaric acid or acetic acid.

5. The method for preparing macroporous silica-alumina gel according to claim 1, characterized in that: The acidic solution described in step (2) is one of ammonium chloride solution, sulfuric acid solution or hydrochloric acid solution.

6. The method for preparing macroporous silica-alumina gel according to claim 1, characterized in that: The microwave reaction conditions described in step (3) are as follows: microwave power is 250-300W, reaction temperature is 60-80°C, and reaction time is 1-3h.

7. The method for preparing macroporous silica-alumina gel according to claim 1, characterized in that: The salt solution described in step (5) is a complex salt solution composed of sodium chloride, lithium chloride and potassium chloride.

8. The method for preparing macroporous silica-alumina gel according to claim 1, characterized in that: The calcination conditions described in step (6) are: calcination temperature is 600-1000° C.; calcination time is 4-8 hours.

9. The macroporous alumino-silica gel prepared by the method for preparing macroporous alumino-silica gel according to claim 1, characterized in that: The specific surface area of ​​the silica-alumina gel is 350-550 m 2 / g, the pore volume is 2.3-3.0mL / g, and the average particle size is 80-130μm.

10. Use of the macroporous silica-alumina gel prepared by the preparation method according to claims 1-8 or the macroporous silica-alumina gel according to claim 9 in catalyzing ethylene polymerization.